Catastrophic outburst and tsunami flooding of Lake Baikal: U–Pb detrital zircon provenance study of the Palaeo-Manzurka megaflood sediments. Issue 14 (25th October 2016) - Ivanov, Alexei V.; Demonterova, Elena I.; Reznitskii, Leonid Z.; Barash, Igor G.; Arzhannikov, Sergey G.; Arzhannikova, Anastasia V.; Hung, Chan-Hui; Chung, Sun-Lin; Iizuka, Yoshiyuki
ABSTRACT: Lake Baikal, the largest freshwater reservoir on Earth (~600 × 30 km in size and up to 1.6 km in depth), has more than 300 contributing rivers but only one N-trending outflow – River Angara. In the Pliocene or Pleistocene, another N-trending outflow operated through the Palaeo-Manzurka to Lena. Provenance analysis using U–Pb dating of detrital zircons from the Palaeo-Manzurka sediments demonstrates that the dominant source of the zircons was the lake deposits, while the contribution of zircons from local bedrocks was limited to about 8% only. Looking for an explanation of this, we propose a hypothesis that formation of the Palaeo-Manzurka sediments took place in association with a catastrophic mega-landslide (~15 × 3 km) into the lake and the resulting mega-tsunami flooding.